Survival status and predictors of mortality among HIV-positive children initiated antiretroviral therapy in Bahir Dar town public health facilities Amhara region, Ethiopia, 2020. (January 2022) - Chekole, Bogale; Belachew, Amare; Geddif, Azeb; Amsalu, Eden; Tigabu, Agimasie
Background: Although there is a presence of governmental and non-governmental organizations running to provide quality HIV care services to reduce HIV-related mortality, there is rapid disease progression and death among children in developing countries including Ethiopia. Thus, this study was aimed to assess the mortality predictors of children living with HIV at Bahir Dar town public health facilities. Method: A facility-based retrospective follow-up study was conducted among 588 children who were enrolled in the HIV care clinic from 1 September 2010 to 30 August 2019. Data were entered into the Epi-Data entry 3.1 and then exported to STATA version 14 for analysis. Multiple imputation models were employed to handle missing data using the multivariate imputation Chained Equations technique. The Kaplan–Meier survival curve and log-rank test were used to estimate and compare the survival time of categorical variables. Result: About 27 (4.6%) (95% confidence interval: 2.9–6.5) deaths were observed from the 30, 062.3 person-months follow-up period, and the overall incidence density rate of 0.9 per 1000 child-months (95% confidence interval: 0.6–1.3). Advanced WHO clinical stage (adjusted hazard ratio = 3.18; 95% confidence interval: 1.07–9.43), hemoglobin level less than 8 g/dL (adjusted hazard ratio = 3.54; 95% confidence interval: 1.27–8.85), children having a weight for age of <−2z (adjusted hazard ratio = 2.81; 95% confidence interval: 1.19–6.6), children with poor adherence (adjusted hazard ratio = 3.91; 95% confidence interval: 1.41–10.8), and starting the treatment beyond 1 week of being eligible (adjusted hazard ratio = 3.22; 95% confidence interval: 1.21–8.53) were predictors of HIV-related mortality among children initiated antiretroviral therapy. Conclusion: The hazard of mortality was higher among HIV-infected children in the early period of initiation. Enhancing antiretroviral therapy drug adherence, monitoring Hgb level, and timely initiation of antiretroviral therapy reduce HIV-related mortality.